IGFBP3-mediated effects of an effective combination therapy on HCC - Lin Chen; Lei Zhao; Guozhi Wu; Tiantian Zhang; Zhiwu Liu; David Fisher; Nguten Thi Thu Hien; Erkin Musabaev (Scientific Reports)
Abstract As all known, hepatocellular carcinoma (HCC) accounts for the majority of cases of liver cancer, which is the third leading cause of cancer mortality globally. Moreover, HCC is always accompanied with HBV infection. Here, we used CMAP, a systematic approach for the discovery of functional connections among diseases and drug actions, to identify quercetin as an effective compound to potentially treat HCC. Furthermore, we proved the inhibitory effects of quercetin on HCC cells, shown as decreased cell viability in HCCLM3 and HepG2 cells. In addition, quercetin disturbed the migration of HCC cells in a dose-dependent manner. Furthermore, quercetin treatments effectively elevated the activities of caspase-3 as well as caspase-9 and increased the Bax expression in HCC cells accompanied with decreased levels of p53 and BCL-2, indicating an enhancement of apoptosis induced by quercetin. Notably, quercetin depressed the activities of antioxidant enzymes, including SOD, GST, GPx and CAT, leading to an increase of ROS accumulation. Additionally, quercetin also exhibited an obvious inhibition of tumor growth of HCC in vivo. Through RNA-seq, results showed that genes related to regulation of cell proliferations were enriched, in which IGFBP3 played a critical role in mediating the effects of quercetin on HCC cells by reducing PI3K-mTOR activation. After silencing IGFBP3 in HCCLM3 cells, quercetin exhibited weaken effects on cell proliferation and apoptosis. Notably, IGFBP3 promotor strengthened the suppressed effects induced by single quercetin administration, indicating a potential drug combination for treatments of HCC. Collectively, this study clarified a novel mechanism underlying the inhibitory effects of quercetin on HCC, providing a potential approach for HCC treatment in clinic.